DEMYSTIFYING THE MYTHS OF SMOOTH EXIT: DECODING TIMELINE OF CORPORATE INSOLVENCY RESOLUTION PROCESS IN INDIA - Mishra, Pihu; Dhall, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The enactment of the Insolvency and Bankruptcy Code signalled a transformative shift in addressing financial distress. Intended to rectify deficiencies in previous bankruptcy regimes, the Code aimed to instigate a cultural metamorphosis within the insolvency resolution process. Nonetheless, despite its ambitious objectives, the IBC has encountered its share of challenges. Adhering to the timeline is one of the many challenges faced by the Code. The paper explores the concept of time bound resolution process under the Code and identifies the challenges in adhering the timeline provisions. The authors highlight the importance of time bound resolution and analyse the impact of delayed resolution on the stakeholders and the market. The research contributes by pointing out the loopholes in the law and the system and exploring alternatives for corporate insolvency resolution process. The paper concludes with the suggestion of amendments that the Code must undergo to pass the test of time.